Handbook of world development : the guide to the Brandt Report - Stephenson, Peter; Brandt, Willy; GJW Government Relations (Firm); Independent Commission on International Development Issues (Harlow : Longman, 1981)
The handbook is an essential reference book that provides the facts about development issues. It outlines the choices in tackling some of the most important issues of the day; and it gives the judgment and advice of the Brandt Commission on the decisions that need to be made about how we use the world's resources for he benefit of everyone, in developed and developing countries alike
Includes bibliographical references: p. 175-177.
osc 28/01/2019
Loans
Keywords: International economic relations; Economic development; Economic history; Developing countries